The Mosaic of Paratextual Thresholds in the Novel “Black Suits You” by Ahlam Mosteghanemi - Tarjat, iman; La'rit, messuda (El Omda in Linguistics and Discourse Analysis, 2022)
This research aims to read the narrative discourse in the series of surrounding textual referrals employed by novelist Ahlam Mostaghanemi in the novel "Black Befits You". Textual thresholds are mosaic panels, formed by drawing and decoration, and created by writing that make the novel a multicolored and multifaceted painting of art, which the reader seeks to realize and reveal the poetic of text , features and interactions between the text and the threshold on the one hand, and the thresholds are related to each other on the other hand.